2021
DOI: 10.1055/a-1678-0002
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Therapy Staffing in the United States and Relationships to Neonatal Intensive Care Unit Type and Location, Level of Acuity, and Population Factors

Abstract: Objectives. To 1) estimate the total pool of neonatal therapists and the average number represented in each US-based NICU, and 2) investigate the relationships between the number and type of neonatal therapy team members to NICU/hospital, population, and therapy factors. Study Design. This study used several methods of data collection (surveys, phone calls, website searches) that were combined to establish a comprehensive list of factors across each NICU in the US. Results. We estimate 2333 neonatal therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…While there are no standards or recommendations for frequency or duration of therapy intervention, evidence suggests that most neonatal therapists, including the therapists in this study, treat infants on their caseload 1–2 times per week on average, and this frequency may increase or decrease based on length of hospitalization, infant medical acuity, and complications of prematurity [ 30 , 31 , 32 ]. Pineda et al conducted a survey-based study published in 2021 that revealed an average of 17 beds per neonatal full-time therapist determined that this ratio was a common indicator of adequate therapy coverage within a NICU [ 27 ]; however, some recommendations that consider the additional non-billable time necessary in neonatal PT and OT practice consider 13–15 infants per FTE more appropriate [ 30 ]. At the time of this study, our NICU had the equivalent of 2.25 full-time OTs and 2.25 full-time PTs in a 65-bed unit.…”
Section: Discussionmentioning
confidence: 99%
“…While there are no standards or recommendations for frequency or duration of therapy intervention, evidence suggests that most neonatal therapists, including the therapists in this study, treat infants on their caseload 1–2 times per week on average, and this frequency may increase or decrease based on length of hospitalization, infant medical acuity, and complications of prematurity [ 30 , 31 , 32 ]. Pineda et al conducted a survey-based study published in 2021 that revealed an average of 17 beds per neonatal full-time therapist determined that this ratio was a common indicator of adequate therapy coverage within a NICU [ 27 ]; however, some recommendations that consider the additional non-billable time necessary in neonatal PT and OT practice consider 13–15 infants per FTE more appropriate [ 30 ]. At the time of this study, our NICU had the equivalent of 2.25 full-time OTs and 2.25 full-time PTs in a 65-bed unit.…”
Section: Discussionmentioning
confidence: 99%
“…The number of staff per bed in a NICU can vary depending on the level of NICU and location of the NICU within the U.S. [ 42 ]. The adequate number of full-time therapists in a Level III/IV NICU with high acuity can be determined via a formula developed by Craig and Smith [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ross et al [ 32 ] reported a level of adequate coverage of a high acuity Level IV NICU according to this formula. In a national survey of NICUs, 97% of Level-IV NICUs and 83% of Level-III NICUs reported having dedicated therapy teams [ 42 ]. Based on this previous work, it may be feasible to increase therapy services for children who need it, particularly OT and PT services given that ST sessions occurred most frequently within three weeks of discharge in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…The PHIS database contains patient- and hospital-level information for 48 academic, pediatric hospitals. This represents one-third of the available academic, pediatric hospitals with level 3/4 neonatal intensive care units (NICUs) [15]. The database is maintained by the Child Health Corporation of America (Shawnee Mission, KS) with data accepted only when coding errors occur in <2% of a hospital’s data [16].…”
Section: Methodsmentioning
confidence: 99%